Legislative policy to criminalizing human trafficking in anti-trafficking law in Saudi Arabia - Ali Naggi, Islam Mahrous (Department of Government Studies, Universitas Muhammadiyah Makassar, 2024)
This research discusses one of the most important crimes against humanity, where national and international statistics and reports revealed that the bad living conditions or bad troubled situations have forced thousands of women, children and men in their countries to be susceptible to the trafficking and exploitation. The study has been divided into two main sections. The first section presents concept of the trafficking in persons in international charters and conventions, reasons, seriousness and elements of the crime in general. The second section studies the Saudi lawmaker's addressing the crime in terms of definition, forms, prescribed penalty and reasons for augmentation of penalty. The study has concluded to a set of results and recommendations, the most important of which is that the Saudi lawmaker adopted position of the international conventions in defining crime and determining its forms. Moreover, the Kingdom has also made great strides in combating this type of crime at both international and local levels. The study recommended the need to impose harsh penalties on employers, who practice patterns of forced slavery to their workers, as well as the need to intensify efforts in order to take adequate measures to prevent smuggling the illegal labor.